2000
DOI: 10.1183/09031936.00.16595900
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 5 and granulocyte-macrophage colony-stimulating factor levels in bronchoalveolar lavage fluid in interstitial lung disease

Abstract: The purpose of this study was to evaluate the role of several eosinophil growth factors including interleukin (IL)-5, interleukin (IL)-3 and granulocyte-macrophage colony-stimulating factor (GM-CSF) in the pathogenesis of interstitial lung disease with eosinophilia. IL-5, IL-3 and GM-CSF in bronchoalveolar lavage fluid (BALF) were measured by enzyme-linked immunosorbent assay (ELISA) in patients with eosinophilic pneumonia (EP), bronchiolitis obliterans organizing pneumonia (BOOP), idiopathic pulmonary fibrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The values recorded here fall slightly below this range (0–41 pg/ml). We could find few estimations of IL-3 concentrations in BALF in the literature but the concentrations recorded here (0.01–0.24 pg/ml) are in agreement with a report where concentrations of less than 1 pg/ml were typical [28]. Even accounting for our small sample set, it is obvious that the IL-3 concentrations used to supplement incubation media in this study and many others [14, 15] far exceed those detected in both serum and BALF.…”
Section: Discussionsupporting
confidence: 64%
“…The values recorded here fall slightly below this range (0–41 pg/ml). We could find few estimations of IL-3 concentrations in BALF in the literature but the concentrations recorded here (0.01–0.24 pg/ml) are in agreement with a report where concentrations of less than 1 pg/ml were typical [28]. Even accounting for our small sample set, it is obvious that the IL-3 concentrations used to supplement incubation media in this study and many others [14, 15] far exceed those detected in both serum and BALF.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, increased GM-CSF levels were observed in BALF of patients with IPF that was associated with increased eosinophilia [11]. These findings may be explained by the effect of GM-CSF on eosinophil survival or eosinophil-specific recruitment [25], which is reflected by the relationship observed between GM-CSF and eosinophils but not neutrophils.…”
Section: Discussionmentioning
confidence: 95%
“…GM-CSF has the capacity to influence proliferation, differentiation and recruitment of eosinophils and is also shown to affect fibroblasts and endothelial cells, potentially resulting in tissue remodelling and angiogenesis [10]. Increased levels of GM-CSF in BALF were found in patients with interstitial lung disease with eosinophilia [11].…”
mentioning
confidence: 99%
“…It plays critical roles in recruiting eosinophils, causing degranulation and prolonging eosinophil survival by inhibiting apoptosis (7)(8)(9). Previous investigations have documented increased concentrations of IL-5 in BAL fluid from patients with eosinophilic pneumonia (10)(11)(12). Furthermore, one study demonstrated that pulmonary eosinophilia in mice could be abrogated by treatment with IL-5 antibodies (13).…”
mentioning
confidence: 97%